La Filosofia di Andy Warhol and the turmoil of art in Italy, 1983 - Francesco Guzzetti (Journal of Art Historiography, 2022)
The article revolves around the first Italian edition of The Philosophy of Andy Warhol. By reconstructing the history of the reception of Warhol in Italy since the 1960s, I position the book within the cultural moment at the turn of the 1980s. I look at the strategies behind the publication and compare it with the original English edition to assess both the editorial presentation and the quality of the translation. Focusing on the similarities as well as the diverging aspects, I argue that the book reinforced the perception of Warhol in Italy as an influential, yet controversial, figure.